Pirouettes on a postage stamp : an interview-novel - Hrabal, Bohumil, 1914-1997 (Beletrie., 2008)
The book is a novel-interview initiated by the Hungarian journalist, writer and anti-communist activist based in Slovakia László Szigeti. It retains the character of a more or less verbatim oral record - it is full of false starts and thematic and syntactic digressions, characteristic for the majority of Hrabalś magical, bizarre and grotesque tales. It is unique for being autobiographical and for making the reader understand Hrabalś personality, his philosophy and perception and understanding of Central Europe shortly before the fall of totalitarian regime in the late 80s.